2003
DOI: 10.1213/01.ane.0000049683.58980.30
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intrathecal Tramadol on Spinal Somatosensory-Evoked Potentials and Motor-Evoked Responses in Rats

Abstract: Spinal somatosensory-evoked potentials and evoked compound muscle action potential were used to evaluate the effects of intrathecal tramadol on sensory and motor neural conduction. Intrathecal tramadol dose-dependently reduced the amplitude and delayed the latency of both spinal somatosensory-evoked potentials and compound muscle action potential. These results indicate that tramadol exerts a dose-related central neural blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Both clinical and basic studies indicated that intrathecal tramadol was useful for pain control [26,27], especially for treating neuropathic pain [3,4]. In accordance with previous reports, the present study showed that intrathecal tramadol attenuated SNL-induced neuropathic pain in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 90%
“…Both clinical and basic studies indicated that intrathecal tramadol was useful for pain control [26,27], especially for treating neuropathic pain [3,4]. In accordance with previous reports, the present study showed that intrathecal tramadol attenuated SNL-induced neuropathic pain in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, Delilkan et al showed that epidural injection of various doses of tramadol (50 and 100 mg) and 0.25% bupivacaine after surgery resulted in better analgesia and longer periods between epidural injections in the 100-mg tramadol group, although nausea and vomiting were also more common in this group (17). In addition to epidural injection of tramadol in humans, it has central-nervous blockade effects when given intrathecally in animals that are dose dependent (18). In addition to the analgesic effects of tramadol, researchers have also studied the drug's anesthetic influences in vitro and found a local anesthetic effect (19).…”
Section: Discussionmentioning
confidence: 99%
“…Jou et al [14] reported that tramadol affects sensory and motor nerve conduction by a similar mechanism to that of lidocaine, which acts on the voltage-dependent sodium channel leading to axonal blockage. Mert et al [7] proposed that tramadol might have a mechanism different from that of lidocaine for producing conduction blocks; the presence of a large Ca 2?…”
Section: Discussionmentioning
confidence: 99%